Clinical Manifestation of Gastroesophageal Reflux among Children with Chronic Constipation - Dehghani, Seyed Mohsen (Middle East J Dig Dis, 2020)
BACKGROUND Functional gastrointestinal system diseases (FGIDs) are a group of childhood disorders, our knowledge of which is relatively limited. More importantly, the different subgroups among such a disease group are closely interrelated, and their natural courses and interrelations have yet to be fully clarified. Functional constipation and gastroesophageal reflux disease (GERD) are most frequently seen among this group. However, evidence as to whether any relationship exists between them is limited. In this study, we tried to examine the existence or absence of this relationship. METHODS First, patients with functional constipation were identified based on ROME III criteria, which included 205 patients. All patients were classified into two groups of 185 and 20 patients based on their ability to respond to the questions. Then age, sex, duration of constipation, treatment, and symptoms associated with reflux were examined based on the GERD questionnaire (in case group 185) and I-GERD (in case group 20). Score > 11 in the GERD questionnaire and score > 15 in the I-GERD questionnaire were considered as reflux disease. The variables that were evaluated using Chi-square and Fisher exact tests using SPSS software version 19 included age, sex, the onset of constipation, constipation duration, duration of treatment of constipation, ROME III criteria, and symptoms associated with reflux. RESULTS In the current study 205 subjects were included (girls = 49.8%, boys = 50.2%). The mean age of the children was 5.51 ± 3.15 years. Among the Rome III criteria, the most frequent were retentive posturing, painful defecation, history of large stool defecation, defecation less than 2 times per week, stool accumulation in the rectum, and fecal incontinency more than once a week, respectively. The lowest symptom among people with chronic constipation was fecal incontinency. Also, 46.8% of all patients in the study had a positive familial history. In general, there were 29 patients (14.1%) with reflux out of the 205 patients with functional constipation. In the present study, no significant relationship was found between Rome III criteria and reflux. CONCLUSION The frequency of GERD among cases with constipation was 14.1%. There was no significant relationship between Rome III criteria and reflux.